Complete chloroplast genome of a wild-type Gardenia jasminoides ellis (rubiaceae) adapted to island climate. Issue 2 (1st February 2021) - Zhang, Min; Chen, Wan-Dong; Li, Yuan-Yuan; Zhang, Cheng; Chai, Zi-Han; Li, Yong-Fu; Xie, Shang-Wei; Deng, Shao-Yong; Duan, Yi-Fan; Wang, Xian-Rong
Abstract: Gardenia jasminoides Ellis is a traditional aromatic and medicinal plant in China. Here, the complete chloroplast genome of a wild-type gardenia adapted to island climate was assembled. The assembled genome was 155, 247 bp in length, with four typical regions, i.e., a large single-copy (LSC) region (85, 414 bp), a small single-copy (SSC) region (18, 235 bp) and two inverted repeats (IRs) regions (25, 799 bp each). In total, 138 genes were predicted, including 90 protein-coding genes, 40 tRNA genes and eight rRNA genes. The overall GC content of the chloroplast genome was 37.5%. The chloroplast genome would provide more information for the phylogeography and phylogeny study of G. jasminoides .